Use of elastin fibre detection in the diagnosis of ventilator associated pneumonia. Issue 1 (January 1995) - el-Ebiary, M; Torres, A; González, J; Martos, A; Puig de la Bellacasa, J; Ferrer, M; Rodriguez-Roisin, R
Abstract : BACKGROUND--Elastin fibre detection could be a simple and reliable marker of ventilator associated pneumonia. To confirm this, a prospective study was undertaken to evaluate the diagnostic yield of elastin fibre detection in the diagnosis of ventilator associated pneumonia. METHODS--Seventy eight mechanically ventilated patients were evaluated by examining endotracheal aspirates for the presence of elastin fibres. All patients were previously treated with antibiotics. Quantitative bacterial cultures of endotracheal aspirates and protected specimen brush samples were also performed. Patients were classified into three diagnostic categories: group 1, definite pneumonia (n = 25); group 2, probable pneumonia (n = 35); and group 3, controls (n = 18). RESULTS--Patients with definite and probable pneumonia were grouped together. The presence of elastin fibres in endotracheal aspirate samples was more frequent in groups 1 and 2, being found in 19 of the 60 patients compared with five of the control group. Although the presence of elastin fibres had a low sensitivity (32%), it was a reasonably specific marker (72%) of pneumonia. This specificity increased to 86% and 81% respectively when only Gram negative bacilli and Pseudomonas aeruginosa pneumonia were considered. Again, calculated sensitivity was 43% and 44% when analysing cases infected by Gram negative bacilli and Ps aeruginosa, respectively. The negative predictive value of the detection of elastin fibres in pneumonia caused by Ps aeruginosa was 81%. Detection was more frequent with infection by Gram negative bacilli (14/19), particularly with Ps aeruginosa (8/14). By contrast, pneumonia due to Gram positive cocci or non-bacterial agents uncommonly resulted in positive elastin fibre preparations (4/19, 21%). When analysing patients with and without chronic obstructive pulmonary disease, the diagnostic value of elastin fibre detection did not change. CONCLUSIONS--Potassium hydroxide preparation of elastin fibres is a rapid and simple specific marker of ventilator associated pneumonia and may be a useful technique to help diagnose pulmonary infections in mechanically ventilated patients, although this assessment is at present limited to patients without adult respiratory distress syndrome.